2018
DOI: 10.1590/s1677-5538.ibju.2017.0146
|View full text |Cite
|
Sign up to set email alerts
|

PCA3 rs544190G>A and prostate cancer risk in an eastern Chinese population

Abstract: Background:The association of prostate cancer antigen 3 (PCA3) polymorphism (SNP, rs544190G>A) with metastatic prostate cancer in European descent has been reported. Our aim of the current study was to re-validate the effect of PCA3 polymorphism on prostate cancer risk in an Eastern Chinese population and then estimate possible genetic discrepancies among population.Materials and Methods:Taqman assay was employed to determine genotype of SNP rs544190 in 1015 ethnic Han Chinese patients with prostate cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Thus, presence of multiple risk alleles is more predictive than a single allele. Another study has reported that SNPs confer a cumulative risk of PCa development [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, presence of multiple risk alleles is more predictive than a single allele. Another study has reported that SNPs confer a cumulative risk of PCa development [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies between results might be attributed to the PCa heterogeneity around the World [ 12 ], location of the SNP [ 22 ] or ethnicity of the studied population, as ethnicity is closely linked to hereditary factors in the genesis of PCa [ 9 , 12 ]. What limits our study is the small sample size, which is attributed to low disease burden in our locality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vitamin D receptor (VDR) rs7975232 SNP was reported to predict PCa risk in African American men [ 23 ]. However, Cao et al [ 24 ] have reported that PCa antigen 3 SNP (rs544190G > A) was associated with metastatic prostate cancer among the European descent but has no association in the Eastern Chinese population. These results exposed the possible ethnicity-associated polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…They have investigated the influence of the IL-8-251T/A SNP on PCa susceptibility and clinicopathological characteristics in Brazilian patients but did not find any association. These divergences in results could be related to the heterogeneity of PCa [ 24 ], location of the SNP on the gene [ 31 ], and/or ethnic differences [ 24 ].…”
Section: Discussionmentioning
confidence: 99%